Transhumance Activities in the Kargapazari Mountains and their Surroundings (North East of Erzurum Province) - Durmus, Esen (Istanbul Univ, Fac Letters, Dept Geography, 2020)
The Eastern Anatolia Region has highly favorable geographical conditions for transhumance. The Erzurum-Kars highlands, Turkey's most important center of transhumant pastoralism, constitute the upper zones of transhumance activities. The concentration of transhumance activities to the north and south of Erzurum also corresponds to the furthest reaches of pastoralism activities. The Kargapazari Mountain Unit, located on the coruh - Kelkit Mountains to the north of Erzurum, constitutes the most important economic utilization area for indigenous and nomadic groups. The nomadic groups in the lower zones, especially flock owners, have greatly benefited from these highlands. The Kargapazari Mountains are the source of three hydrographic basins. In addition to wide meadows and pastures, the area consists of a high plateau and snow stays on the ground for 110-120 days, making this area one of Turkey's most important transhumance centers. Besides the villages, there are hamlets, mountain houses and plateau settlements as well. The nomadic groups coming to the Kargapazan Mountains from the provinces of Elazig, Diyarbakir, Urfa and Tunceli mostly climb up to Buyukdere, Wren, Timar, Senyurt, Kosk, Buyuktay, Sercebogazi to find summer pasture for their animals. Even though the duration of this transhumance activity depends on the specific altitude of each location, it is generally carried out between the months of June and September.
Keywords: Transhumance; Kargapazari; Settlementtype